AIK1, A Mitogen-Activated Protein Kinase, Modulates Abscisic Acid Responses through the MKK5-MPK6 Kinase Cascade. Issue 2 (2nd December 2016) - Li, Kun; Yang, Fengbo; Zhang, Guozeng; Song, Shufei; Li, Yuan; Ren, Dongtao; Miao, Yuchen; Song, Chun-Peng
Abstract : An Arabidopsis MAPK kinase kinase (MAPKKK), AIK1, modulates ABA signaling by sequentially relaying and amplifying intracellular signals through the AIK1-MKK5-MPK6 cascade. Abstract: The mitogen-activated protein kinase (MAPK ) cascade is an evolutionarily conserved signal transduction module involved in transducing extracellular signals to the nucleus for appropriate cellular adjustment. This cascade essentially consists of three components: a MAPK kinase kinase (MAPKKK ), a MAPK kinase, and a MAPK, connected to each other by the event of phosphorylation. Here, we report the characterization of a MAPKKK, ABA-INSENSITIVE PROTEIN KINASE1 (AIK1), which regulates abscisic acid (ABA ) responses in Arabidopsis ( Arabidopsis thaliana ). T-DNA insertion mutants of AIK1 showed insensitivity to ABA in terms of both root growth and stomatal response. AIK1 functions in ABA responses via regulation of root cell division and elongation, as well as stomatal responses. The activity of AIK1 is induced by ABA in Arabidopsis and tobacco ( Nicotiana benthamiana ), and the Arabidopsis protein phosphatase type 2C, ABI1, a negative regulator of ABA signaling, restricts AIK1 activity by dephosphorylation. Bimolecular fluorescence complementation analysis showed that MPK3, MPK6, and AIK1 interact with MKK5. The single mutant seedlings of mpk6 and mkk5 have similar phenotypes to aik1, but mkk4 does not. AIK1 was localized in the cytoplasm and shown to activate MKK5 by protein phosphorylation, which was an ABA-activated process. Constitutively active MKK5 in aik1 mutant seedlings complements the ABA-insensitive root growth phenotype of aik1 . The activity of MPK6 was increased by ABA in wild-type seedlings, but its activation by ABA was impaired in aik1 and aik1 mkk5 mutants. These findings clearly suggest that the AIK1-MKK5-MPK6 cascade functions in the ABA regulation of primary root growth and stomatal response.